Systematic Literature Review of Interior Design in Virtual Reality Environment - Muhammad Nur Aiman Doktah @ Mokhtar,; Ismahafezi Ismail,; Wan Mohd Amir Fazamin Wan Hamzah,; Maizan Mat Amin,; Fazida Karim,; Addy Putra Md Zulkifli, (Journal of Advanced Research in Applied Sciences and Engineering Technology, 2023)
The purpose of the current paper is to review the potential interior design in virtual reality environment. Therefore, in this systematic literature review, we analyse findings on virtual reality interior design and disseminate this information as a written overview of current studies. Six papers were selected after 146 papers from Scopus databases were shortlisted and subjected to various inclusion and exclusion criteria. Virtual reality has the potential to be a tool for interior designers when it comes to design. Future research can gather more thorough data by incorporating conference articles and merging information from various databases.